Effect of growth temperature on the high stearic and high stearic-high oleic sunflower traits. - Izquierdo, Natalia Gabriela (2013)
We investigated variability in the response of oil fatty acid composition to temperature among high stearic and high stearic-high oleic sunflower (Helianthus annuus L.) genotypes. Two experiments were conducted with high stearic (including theCAS-3mutation) and high stearic-high oleic inbred lines (including both theCAS-3 and the high oleic Soldatov mutations). Plants were cultivated in pots with soil, irrigated, and fertilised. Plants were exposed to different day/night temperatures during grain filling: 16/168C, 26/168C, 26/268C, and 32/268C. Oil fatty acid composition was determined by gas–liquid chromatography in seeds harvested after physiological maturity. Higher temperature during grain filling increased palmitic and oleic acid percentages and reduced stearic and linoleic acid percentages, suggesting some modifications on enzymatic activities. When the high oleic mutation was included, the variation in stearic and oleic acid percentages in response to temperature was reduced but not the variation in palmitic acid concentration. Variations in fatty acid composition in high stearic genotypes were mainly associated with night temperature as reported previously for traditional and high oleic hybrids. Knowing the effect of temperature on oil fatty acid composition in traditional and mutated genotypes is useful for selecting the environment in which to produce grains with the desired oil quality.